The Problems in Implementing the Function of the Integrated Law Enforcement Center (Gakkumdu) as an Election Law Enforcement Institution - Faizal, Liky (As-Siyasi: Journal of Constitutional Law, 2023)
The Integrated Law Enforcement Center, hereinafter referred to as Gakkumdu, is the center of law enforcement activities for election crimes consisting of elements. The purpose of establishing Gakkumdu is to encourage the election judicial process to take place quickly and accurately. This research aims to analyze the implementation of the Sentra Gakkumdu function in Lampung Province and the inhibiting factors in the implementation of the Sentra Gakkumdu function in election law enforcement in Lampung Province. The results showed that the implementation of the function of the Sentra Gakkumdu in law enforcement of election criminal offenses by the Sentra Gakkumdu in the elections in Lampung Province was ineffective. This can be seen from the many cases handled; not all of them have been followed up on by the Gakkumdu center. The main problem in implementing the law enforcement function of election crimes by the Gakkumdu center is that there are often differences in legal perceptions among Gakkumdu members in determining whether a violation meets the elements of an election violation.